Simplify the radical expression\sqrt[3]{11a^2/64b^6}

defazajx 2021-09-20 Answered

Simplify the radical expression
\(\sqrt[3]{\frac{11a^2}{64b^6}}\)

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Expert Answer

Aniqa O'Neill
Answered 2021-09-21 Author has 23240 answers

Simplilfying the given radical expression (involving fractional exponents) means removing roots as much as possible, using the laws of exponents (powers)
First apply the rule
\(\sqrt[n]{\frac{x}{y}}=\sqrt[n]{\frac{x}{\sqrt[n]{y}}}\)
Here, \(\displaystyle{x}={11}{a}^{{2}},{y}={64}{b}^{{6}}={\left({4}\right)}^{{3}}{b}^{{6}}={\left({4}{b}^{{2}}\right)}^{{3}}\)
So,
\(\sqrt[3]{\frac{11a^2}{64b^6}}=\sqrt[3]{\frac{{11a^2}}{\sqrt[3]{(4b^2)^3}}}\)
Note: the numerator (radical ) cannot be simplified as none of the factors 11 or a^2 is a cube. On the other hand, the denominator radical can be simplified , as it is a cube.
Now apply the rule
\(\sqrt[n]{z^k}=(z^k)^{\frac{1}{n}}=z^{\frac{k}{n}}\)
Here, \(\displaystyle{z}={4}{b}^{{2}},{k}={3},{n}={3}\)
So,
\(\sqrt[3]{(4b^2)^3}=(4b^2)^{\frac{3}{3}}=4b^2\)
Answer: \(\sqrt[3]{\frac{11a^2}{64b^6}}=\frac{\sqrt[3]{11a^2}}{4b^2}\)

Not exactly what you’re looking for?
Ask My Question
0
 

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more
...